High-performance aramid fiber composite conductive fiber and preparation method and preparation system thereof
By preparing the conductive core layer of the PU meltblown intermediate layer and the liquid metal mixed solution, and thermally bonding it with the aramid core yarn skin, the problem of poor conductivity of existing conductive fibers is solved, and high-performance aramid composite conductivity is achieved The fiber preparation has excellent electrical conductivity, mechanical and fire-resistant and thermal insulation properties.
Patent Information
- Application Number
- CN202411463719.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The conductive properties of existing conductive fibers are not superior and durable enough, and the conductive layer is easily damaged on the outer layer of the fiber, affecting the conductivity and safety.
A high-performance aramid composite conductive fiber is used to prepare a PU meltblown intermediate layer and a liquid metal mixed solution conductive core layer, and thermally bonded with the aramid core yarn skin to form composite conductive fibers.
It realizes high-performance aramid composite conductive fiber with excellent conductivity, good mechanical properties and high fire resistance and heat insulation performance. It does not require chemical reagents for bonding during the production process. The conductive core material is a gallium indium tin liquid alloy, which is non-toxic and non-toxic. It is harmful to green and environmental protection.
Smart Images

Figure CN119392420A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite conductive fiber preparation, and in particular to a high-performance aramid composite conductive fiber and a preparation method and a preparation system thereof. Background Art
[0002] With the rapid development of smart flexible wearable textiles and smart home industries, conductive fibers with higher flexibility and safety have gradually become a hot research direction in the field of flexible conductive materials. Researchers have begun to explore composite conductive materials with higher safety factors, better performance, excellent conductivity, and the ability to achieve lightweight production.
[0003] In the prior art, the preparation methods of conductive fibers mostly use solution spinning to prepare single fiber filaments as a substrate or MXene as a functional composite conductive core layer, and then use conductive coatings for coating finishing. After surface modification, chemical groups are grafted or the surface of the filaments is etched to add a conductive dispersion. However, the conductive properties obtained in this way are often not superior and durable enough, and the conductive layer is on the outer layer of the fiber, and its surface is easily damaged and causes safety hazards, while affecting its conductivity and safety.
[0004] For example, patent CNCN116815494A proposes a method for preparing aramid conductive fiber, using ultrasonic swelling to form microcracks on the surface of aramid fiber, and finally filling the surface of aramid fiber and the inside of microcracks with conductive filler dispersion. The mechanical properties of the aramid composite conductive fiber obtained by this method mainly rely on the properties of the aramid fiber itself, and cannot give play to the structural advantages of the composite material. At the same time, the uniformity of the conductive seasoning dispersion has a great influence on the conductive properties of the composite conductive fiber, resulting in the electrical properties of the aramid composite conductive fiber being not stable enough. Patent CN113235184B proposes a skin-core structured aramid composite conductive fiber, which is obtained by wet solution spinning to obtain aramid nanofibers as the skin layer, aramid nanofibers and MXene-based composite conductive fibers as the core layer, and finally the skin layer and the core layer are composited by coagulation bath curing. The aramid composite conductive fiber prepared by this method is a nanofiber with good conductive properties, but the fiber diameter is too thin, which is not conducive to practical application in most cases, and the load current that can be sustained is also small, and lightweight production is difficult. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present application proposes a high-performance aramid composite conductive fiber and a preparation method and system thereof, which have excellent conductivity and ductility while improving the fireproof and heat-insulating properties of the conductive fiber.
[0006] The following is a technical solution of the present invention, a method for preparing a high-performance aramid composite conductive fiber, comprising the following steps:
[0007] S1, preparing PU melt-blown preform;
[0008] S2, preparing a liquid metal mixed solution;
[0009] S3, while preparing the PU melt-blown middle layer, pouring the liquid metal mixed solution into the PU melt-blown middle layer;
[0010] S4, thermally bonding the PU melt-blown middle layer and the aramid core-spun yarn to obtain aramid composite conductive fibers.
[0011] As a preference, the specific steps of S1 are as follows:
[0012] The polyurethane slices are made into PU melt-blown cloth by melt-blowing process, and the PU melt-blown cloth is wound on the stainless steel pipe in a layered structure. The PU melt-blown cloth on the stainless steel pipe is heated by an annular ultrasonic heating device to soften and bond it, and the steel pipe is removed to obtain a PU melt-blown preform rod;
[0013] Among them, the melt index of the polyurethane chip is 280g / (10min), the melt temperature is 210℃, the spinning speed is 200m / min, the wind speed is 200m / min, and the receiving distance is 20cm; the surface density of the PU meltblown cloth is 1.2-1.3g / cm3, and the thickness is 0.2-0.3mm; the outer diameter of the stainless steel tube is 12mm, the number of winding layers of the PU meltblown cloth is 5-6 layers, and the heating temperature of the annular ultrasonic heating device is 180-200℃.
[0014] Preferably, the specific steps of S2 are as follows:
[0015] The gallium indium tin liquid metal is immersed in a hydrochloric acid solution, and after standing, it is washed with anhydrous ethanol, and magnesium nanoparticles are added, and stirred evenly with a magnetic stirrer to obtain a liquid metal mixed solution in which magnesium nanoparticles are evenly mixed;
[0016] The concentration of the hydrochloric acid solution is 5%-20%, the concentration of anhydrous ethanol is 99.9%, the mass ratio of gallium indium tin liquid metal and magnesium nanoparticles ranges from 1:1 to 10:1, the diameter of the magnesium nanoparticles is 5-10nm, and the rotation speed of the magnetic stirrer is 600-800r / min.
[0017] As a preference, the specific steps of S3 are as follows:
[0018] The bottom ends of the PU melt-blown preform rods are bonded together in a ring-shaped ultrasonic heating device, and the PU melt-blown preform rods are shrunk and thinned by the thermal stretching principle until they are stretched into a fiber-like PU melt-blown middle layer;
[0019] Among them, the drawing speed is 2cm / s, the diameter of the PU melt-blown middle layer is 1.5-2.0mm, the temperature of the upper temperature zone is 190-210℃, the temperature of the middle temperature zone is 150-170℃, and the temperature of the lower temperature zone is 110-130℃;
[0020] While the PU melt-blown intermediate layer is being hot-stretched, the prepared liquid metal mixed solution is infused into the PU melt-blown intermediate layer of the PU melt-blown preform from the top opening of the PU melt-blown preform by using a syringe pump;
[0021] Among them, the hot stretching temperature range is 100-190°C, the diameter of the PU melt-blown middle layer is 0.3-0.4mm, the injection pump flow rate is 226.2ml / h, and the injection pump needle diameter is 1.5mm.
[0022] Preferably, the specific steps of S4 are as follows:
[0023] Aramid filaments and aramid rovings are twisted with the PU melt-blown middle layer in the form of sirofil spinning, and the residual heat during the hot stretching process is used to make the surface of the PU melt-blown middle layer thermally bonded with the aramid core-spun yarn in a softened state to obtain aramid composite conductive fibers;
[0024] The diameter of the aramid filament is 0.02-0.03 mm, the twisting speed of the aramid core-spun yarn is 80-100 TPM, and the surface temperature of the PU melt-blown middle layer is 140-150°C.
[0025] A high-performance aramid composite conductive fiber comprises: a mixed solution conductive core layer, the mixed solution conductive core layer is connected to a PU melt-blown middle layer, and the PU melt-blown middle layer is thermally twisted with aramid filaments and aramid rovings by a sirofil spinning process to form an aramid core-spun yarn skin layer.
[0026] A high-performance aramid composite conductive fiber preparation system, comprising:
[0027] Meltblown cloth winding device, used to wind PU meltblown cloth on stainless steel pipe;
[0028] The annular ultrasonic heating device is used to uniformly point-bond the PU melt-blown cloth wound on the stainless steel tube to obtain a PU melt-blown preform rod, which is connected to the melt-blown cloth winding device;
[0029] The drawing tower hot stretching device is used to hot stretch the prepared PU melt-blown preform rod and is connected to the annular ultrasonic heating device;
[0030] A mixed solution injection device is used to inject the liquid metal mixed solution into the PU melt-blown middle layer of the PU melt-blown preform rod, and is connected to the drawing tower hot stretching device;
[0031] The Serofel spinning device is used to prepare aramid core-spun yarn and is connected to the drawing tower hot stretching device.
[0032] Preferably, the drawing tower hot stretching device comprises:
[0033] A spatial position control module, used to control the position of the suspended PU melt-blown preform;
[0034] Laser diameter measuring and plane position measuring instrument, used to define the diameter of PU melt-blown preform during hot stretching;
[0035] The pressure adjustment module is used to limit the pressure applied to the PU melt-blown preform during hot stretching;
[0036] Fiber position limiting module, used to limit the position of PU melt-blown preform during hot stretching;
[0037] Wire drawing module, used for winding and collecting fibers obtained after shrinking and thinning PU melt-blown preform rods;
[0038] An inert gas delivery module is used to control the thermal stretching conditions in the three temperature zones;
[0039] The heating furnace temperature control module is used to control the thermal stretching conditions in the three temperature zones;
[0040] High temperature heating module, used to heat PU melt-blown preform;
[0041] Preform hanging module, used to hang PU melt-blown preform;
[0042] Concentricity control module for fine tuning the center of the produced fiber.
[0043] Preferably, the Serofel spinning device comprises:
[0044] A filament winding module, used for feeding and winding filaments;
[0045] A roving winding module, used for inputting and winding roving;
[0046] Tension disk, used to adjust the tension of the filaments so that the filaments are evenly set;
[0047] The godet is used to draw the filaments and rovings and connect the filaments and rovings;
[0048] Front roller, used to twist filaments and rovings to form aramid core-spun yarn;
[0049] Core yarn winding module for finishing and recycling aramid core yarn.
[0050] Beneficial effects of the present invention:
[0051] 1. The high-performance aramid composite conductive yarn provided by the present invention has a PU middle layer with uniform interlayer gaps, has excellent bonding effect, and has excellent structural mechanical properties. The composite effect with the liquid conductive metal core layer and the aramid core-covered yarn skin layer is excellent. The aramid composite conductive fiber has both flexibility and mechanical properties, and has excellent conductive properties and fireproof and heat-insulating properties, which greatly improves the practical performance and safety performance of the conductive material. In the production process of the composite material, no chemical reagents are required for bonding. At the same time, the conductive core material is a gallium-indium-tin liquid alloy, which is non-toxic, harmless, green and environmentally friendly.
[0052] 2. The electrical conductivity of the aramid composite conductive fiber is 5600S / m. According to the GB / T 5455-2014 implementation standard, the fire protection level measured is V-0, which means that the sample will self-extinguish under the test flame and the burning time is very short. The tensile breaking strength is 890MPa, which has excellent mechanical properties and an elongation at break of 7%, which effectively enhances the ductility of the aramid composite fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 It is a schematic diagram of the structure of the high-performance aramid composite conductive fiber of the present invention;
[0054] Figure 2 This is a flow chart of the method for preparing high-performance aramid composite conductive fibers of the present invention;
[0055] Figure 3 This is a PU melt-blown cloth winding diagram of the high-performance aramid composite conductive fiber preparation method of the present invention;
[0056] Figure 4 Schematic diagram of the preparation system of the high-performance aramid composite conductive fiber of the present invention Figure 1 ;
[0057] Figure 5 Schematic diagram of the preparation system of the high-performance aramid composite conductive fiber of the present invention Figure 2 ;
[0058] Figure 6 It is a schematic diagram of a ring-shaped ultrasonic heating device of the high-performance aramid composite conductive fiber preparation system of the present invention;
[0059] Figure 7 It is a schematic diagram of a drawing tower hot stretching device of the high-performance aramid composite conductive fiber preparation system of the present invention;
[0060] Figure 8 A schematic diagram of a sirofil spinning device of a high-performance aramid composite conductive fiber preparation system of the present invention;
[0061] In the figure: 1. Annular ultrasonic heating device; 2. Drawing tower hot stretching device; 3. Sirofil spinning device; 4. Meltblown cloth winding device; 5. Mixed solution injection device; 6. Mixed solution conductive core layer; 7. PU meltblown middle layer; 8. Aramid core yarn skin layer; 201. Spatial position control module; 202. Laser diameter measurement and plane position measuring instrument; 203. Pressure adjustment module; 204. Fiber position limitation module; 205. Drawing module; 206. Inert gas delivery module; 207. Heating furnace temperature control module; 208. Hot drawn yarn; 209. High temperature heating module; 210. Preform rod suspension module; 211. Concentricity control module; 301. Filament winding module; 302. Roving winding module; 303. Tension disk; 304. Front roller; 305. Godet wheel; 306. Core yarn winding module. DETAILED DESCRIPTION
[0062] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention will be further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0063] Embodiment 1:
[0064] like Figure 1 As shown, a high-performance aramid composite conductive fiber includes: a mixed solution conductive core layer 6, a PU melt-blown middle layer 7, and an aramid core-spun yarn skin layer 8.
[0065] The mixed solution conductive core layer 6 is a liquid metal conductive solution obtained by uniformly mixing a gallium indium tin liquid metal solution after surface deoxidation treatment and magnesium nanoparticles;
[0066] PU melt-blown intermediate layer 7, the PU melt-blown intermediate layer 7 is a layered gap-bonded intermediate layer, and the layered wound PU melt-blown fabric is evenly point-bonded and then thermally stretched to obtain the PU melt-blown intermediate layer 7;
[0067] The aramid core-spun yarn skin layer 8 is formed by bonding the aramid filaments and aramid rovings with the PU melt-blown intermediate layer 7 by using the Sirofil spinning process.
[0068] The mixed solution conductive core layer 6 of the aramid composite conductive fiber is a gallium-indium-tin liquid metal mixed solution, and the outside of the mixed solution conductive core layer 6 is a PU melt-blown intermediate layer 7. The aramid filaments and aramid rovings are twisted with the PU melt-blown intermediate layer 7 by the Sirofil spinning process, and then thermally bonded to form an aramid core-spun yarn skin layer 8.
[0069] The PU meltblown intermediate layer 7 is made by meltblowing, layered winding and gap bonding, and has good ductility and mechanical properties. It is then stretched, tightened and refined at a relatively low temperature. While retaining the interlayer gap in a low temperature state, the treated and mixed gallium, indium and tin liquid alloy metal is injected, which can effectively increase the effective contact area between the liquid alloy and the intermediate layer, enhance the conductivity and stability of the mixed solution conductive core layer 6, and utilize the residual heat during hot stretching to evenly and densely compound the aramid yarn and the PU meltblown intermediate layer 7 in the form of sirofil spinning and thermal bonding.
[0070] Embodiment 2:
[0071] like Figure 2 As shown, a method for preparing a high-performance aramid composite conductive fiber comprises the following steps:
[0072] S1, preparing PU melt-blown preform;
[0073] S2, preparing a liquid metal mixed solution;
[0074] S3, while preparing the PU melt-blown intermediate layer 7, pouring the liquid metal mixed solution into the PU melt-blown intermediate layer 7;
[0075] S4, thermally bonding the PU melt-blown intermediate layer 7 and the aramid core-spun yarn to obtain aramid composite conductive fibers.
[0076] In step S1, a PU melt-blown preform is prepared. Figure 3 As shown, the PU nonwoven fabric (i.e., PU meltblown fabric) obtained by meltblowing is wound on a stainless steel pipe in a layered structure, and then the PU meltblown fabric on the steel pipe is heated by a ring-shaped ultrasonic heating device 1 to soften and bond together, and then the steel pipe is removed to obtain a PU meltblown preform. The softening temperature is controlled so that the PU meltblown fabric with a layered structure is partially bonded to form interlayer gaps between different meltblown layers, so that the flexibility and mechanical properties of the composite conductive fiber finally obtained are improved.
[0077] Specifically, a PU nonwoven fabric roll is manufactured from polyurethane slices using a melt-blown process, and the PU nonwoven fabric manufactured by the melt-blown process is wound on a stainless steel tube with a diameter of 12 mm, with the number of winding layers being 5-6 layers, and then the layered wound PU melt-blown fabric is uniformly point-bonded using an annular ultrasonic heating device 1 to obtain a PU melt-blown preform rod;
[0078] The meltblown process parameters of the PU meltblown fabric are as follows: the melt index (MFI) of the polyurethane chips used is 280g / (10min); the melt temperature is 210°C; the spinning speed is 200m / s; the hot stretching air flow speed is 200m / s; and the receiving distance is 20cm. The surface density of the PU meltblown fabric is 1.26g / cm 3 , thickness is 0.2mm.
[0079] In step S2, a liquid metal mixed solution is prepared. Gallium indium tin liquid metal is poured into a hydrochloric acid solution, the hydrochloric acid covers the gallium indium alloy, and the solution is allowed to stand to obtain a liquid metal solution, which is then washed with anhydrous ethanol, and finally magnesium nanoparticles are added and stirred evenly with a magnetic stirrer to obtain a gallium indium liquid metal mixed with magnesium nanoparticles.
[0080] Specifically, gallium indium tin liquid metal is poured into a hydrochloric acid solution with an equivalent concentration of 0.01 mol / L until the hydrochloric acid solution submerges the liquid metal solution, and the solution is allowed to stand for 4 hours to obtain a liquid metal solution after surface treatment, which is then washed with 99% anhydrous ethanol and dried. Finally, magnesium nanoparticles with an average diameter of 7 nm are added, and the mass ratio of liquid metal to magnesium nanoparticles is 4:1. The liquid metal solution containing magnesium nanoparticles is stirred evenly using a magnetic stirrer with a rotation speed of 800 r / min to obtain a gallium indium liquid metal mixed with magnesium nanoparticles evenly (i.e., a mixed solution conductive core layer 6).
[0081] Gallium indium tin liquid metal is poured into a beaker, and an acidic solution is used to remove the oxide layer in the gallium indium liquid metal, while reducing the surface tension of the liquid metal. Magnesium nanoparticles are doped into the treated gallium indium liquid metal to increase wettability while maintaining high conductivity and ductility.
[0082] In step S3, while preparing the PU melt-blown intermediate layer 7, the liquid metal mixed solution is poured into the PU melt-blown intermediate layer 7. To prepare the PU melt-blown intermediate layer 7, specifically, the PU melt-blown preform rod is hung in the drawing tower hot stretching device 2, and the bottom ends thereof are bonded together, and the PU melt-blown preform rod is shrunk and thinned by the hot stretching principle until it is stretched into a fiber-shaped PU melt-blown intermediate layer 7;
[0083] Among them, the temperatures of the three temperature zones of the drawing tower hot stretching device 2 are: the temperature of the upper temperature zone is 190°C, the temperature of the middle temperature zone is 150°C, and the temperature of the lower temperature zone is 110°C; the drawing speed of the preform rod is 2cm / s, and the diameter of the PU melt-blown intermediate layer 7 of the prepared hollow fiber is 2.0mm.
[0084] While preparing the PU melt-blown intermediate layer 7, the liquid metal mixed solution is poured into the PU melt-blown intermediate layer 7. Specifically, while the PU melt-blown intermediate layer 7 is being hot-stretched, the prepared liquid metal mixed solution is poured into the PU melt-blown intermediate layer 7 of the PU melt-blown preform from the top opening of the PU melt-blown preform by using an injection pump, so that the pouring of the mixed solution conductive core layer 6 and the tightening and thinning of the PU melt-blown intermediate layer 7 are carried out simultaneously, further enhancing the effective contact and stability of the mixed solution conductive core layer 6 and the PU melt-blown intermediate layer 7;
[0085] Among them, the injection pump flow rate of the liquid metal mixed solution is 226.2 ml / h, the injection pump needle diameter is 1.5 mm, and the average diameter of the PU hollow fiber after stretching and thinning is 2 mm in inner diameter and 2.7 mm in outer diameter.
[0086] When the PU melt-blown preform is stretched and thinned in the hot stretching device 2 of the drawing tower, it is necessary to monitor and control its temperature changes in the three temperature zones of 100-190°C, so that the interlayer gap of the PU melt-blown cloth can be relatively intactly preserved, and at the same time, the PU melt-blown preform is compacted and thinned. At this time, the PU melt-blown preform is in a viscoelastic state, and its top is the PU melt-blown intermediate layer 7 after stretching and thinning, and the bottom becomes a solid section of the PU fiber due to bonding together. At this time, the prepared gallium-indium liquid metal mixed solution is infused into the PU melt-blown intermediate layer 7 using the syringe pump needle, so that the infusion of the mixed solution conductive core layer 6 and the compaction and thinning of the PU melt-blown intermediate layer 7 are carried out simultaneously.
[0087] In step S4, the PU melt-blown intermediate layer 7 and the aramid core-spun yarn are thermally bonded to obtain aramid composite conductive fibers. Specifically, the aramid filaments and aramid rovings are twisted with the PU melt-blown intermediate layer 7 in the form of sirofil spinning by using the sirofil spinning device 3, and the residual heat during the hot stretching process is used to thermally bond the surface of the PU melt-blown intermediate layer 7 with the aramid core-spun yarn in a softened state to obtain aramid composite conductive fibers;
[0088] The diameter of the aramid filament is 0.02 mm, the twisting speed of the aramid core-spun yarn is 80 TPM, and the surface temperature of the PU melt-blown intermediate layer 7 is 100° C. during thermal bonding.
[0089] Embodiment 3:
[0090] Different from Example 2, this example changes the number of winding layers of the preform rod, changing the number of winding layers in Example 2 from 5-6 layers to 8-9 layers in this example.
[0091] A method for preparing high-performance aramid composite conductive fiber comprises the following steps:
[0092] S11, preparing PU melt-blown preform;
[0093] The PU nonwoven fabric manufactured by the melt-blown process is wound on a stainless steel tube with a diameter of 12 mm, and the number of winding layers is 8-9 layers. Then, the layered PU melt-blown fabric is evenly point-bonded by a ring-shaped ultrasonic heating device 1 to obtain a PU melt-blown preform;
[0094] The meltblown process parameters of the PU meltblown fabric are: the melt index (MFI) of the polyurethane chips used is 280g / (10min); the melt temperature is 190℃; the receiving distance is 20cm. The surface density of the PU meltblown fabric is 1.2-1.3g / cm3 and the thickness is 0.2-0.3mm.
[0095] S12, preparing a liquid metal mixed solution;
[0096] Gallium, indium, and tin liquid metal is poured into a hydrochloric acid solution with an equivalent concentration of 0.01 mol / L until the hydrochloric acid solution submerges the liquid metal solution, and the solution is allowed to stand for 4 hours to obtain a liquid metal solution after surface treatment, which is then washed with 99% anhydrous ethanol and dried. Finally, magnesium nanoparticles with a diameter of 7 nm are added, and the mass ratio of liquid metal to magnesium nanoparticles is 4:1. The liquid metal solution containing magnesium nanoparticles is stirred evenly using a magnetic stirrer with a rotation speed of 800 r / min to obtain a gallium-indium liquid metal mixed solution with magnesium nanoparticles evenly mixed.
[0097] S13, while preparing the PU melt-blown intermediate layer 7, pouring the liquid metal mixed solution into the PU melt-blown intermediate layer 7;
[0098] Preparation of PU melt-blown intermediate layer 7: Hanging the PU melt-blown preform rod in the drawing tower hot stretching device 2, bonding the bottom ends together, and using the hot stretching principle to make the PU melt-blown preform rod compact and thin until it is stretched into a fiber-shaped PU melt-blown intermediate layer 7;
[0099] Among them, the temperatures of the three temperature zones of the drawing tower hot stretching device 2 are: the temperature of the upper temperature zone is 190°C, the temperature of the middle temperature zone is 150°C, and the temperature of the lower temperature zone is 110°C; the drawing speed of the preform rod is 2cm / s, and the diameter of the PU melt-blown intermediate layer 7 of the prepared hollow fiber is 1.8mm;
[0100] At the same time, the liquid metal mixed solution is poured into the PU melt-blown intermediate layer 7: while the PU melt-blown intermediate layer 7 is being hot-stretched, the prepared liquid metal mixed solution is poured into the PU melt-blown intermediate layer 7 of the PU melt-blown preform from the top opening of the PU melt-blown preform by using an injection pump, so that the pouring of the mixed solution conductive core layer 6 and the tightening and thinning of the PU melt-blown intermediate layer 7 are carried out at the same time, further enhancing the effective contact and stability of the mixed solution conductive core layer 6 and the PU melt-blown intermediate layer 7;
[0101] Among them, the injection pump flow rate of the liquid metal is 226.2 ml / h, the injection pump needle diameter is 1.5 mm, and the diameter range of the PU hollow fiber after stretching and thinning is: inner diameter is 1.8 mm, and outer diameter is 2.9 mm.
[0102] S4, thermally bonding the PU melt-blown intermediate layer 7 and the aramid core-spun yarn to obtain aramid composite conductive fibers;
[0103] Aramid filaments and aramid rovings are twisted with the PU melt-blown intermediate layer 7 in the form of sirofil spinning, and the residual heat during the hot stretching process is used to make the surface of the PU melt-blown intermediate layer 7 thermally bonded with the aramid core-spun yarn in a softened state to obtain aramid composite conductive fibers;
[0104] The diameter of the aramid filament is 0.02 mm, the twisting speed of the aramid core-spun yarn is 80 TPM, and the surface temperature of the PU melt-blown intermediate layer 7 is 100° C. during thermal bonding.
[0105] Embodiment 4:
[0106] Different from Example 2, this example changes the temperatures of the three temperature zones of the drawing tower hot stretching device 2, changing the temperature of the upper temperature zone in Example 2 from 190°C to 210°C, the temperature of the middle temperature zone from 150°C to 170°C, and the temperature of the lower temperature zone from 110°C to 130°C.
[0107] A method for preparing high-performance aramid composite conductive fiber comprises the following steps:
[0108] S21, preparing PU melt-blown preform;
[0109] The PU nonwoven fabric manufactured by the melt-blown process is wound on a stainless steel tube with a diameter of 12 mm, and the number of winding layers is 5-6. Then, the layered PU melt-blown fabric is evenly point-bonded by a ring-shaped ultrasonic heating device 1 to obtain a PU melt-blown preform rod;
[0110] The meltblown process parameters of the PU meltblown fabric are: the melt index (MFI) of the polyurethane chips used is 280g / (10min); the melt temperature is 210°C; the spinning speed is 200m / s; the hot stretching air flow speed is 200m / s; the receiving distance is 20cm. The surface density of the PU meltblown fabric is 1.26g / cm3 and the thickness is 0.2mm.
[0111] S22, preparing a liquid metal mixed solution;
[0112] Gallium, indium, and tin liquid metal is poured into a hydrochloric acid solution with an equivalent concentration of 0.01 mol / L until the hydrochloric acid solution submerges the liquid metal solution, and the solution is allowed to stand for 4 hours to obtain a liquid metal solution after surface treatment, which is then washed with 99% anhydrous ethanol and dried. Finally, magnesium nanoparticles with an average diameter of 7 nm are added, and the mass ratio of liquid metal to magnesium nanoparticles is 4:1. The liquid metal solution containing magnesium nanoparticles is stirred evenly using a magnetic stirrer with a rotation speed of 800 r / min to obtain a gallium-indium liquid metal mixed solution with magnesium nanoparticles evenly mixed.
[0113] S23, while preparing the PU melt-blown intermediate layer 7, pouring the liquid metal mixed solution into the PU melt-blown intermediate layer 7;
[0114] Preparation of PU melt-blown intermediate layer 7: Hanging the PU melt-blown preform rod in the drawing tower hot stretching device 2, bonding the bottom ends together, and using the hot stretching principle to make the PU melt-blown preform rod compact and thin until it is stretched into a fiber-shaped PU melt-blown intermediate layer 7;
[0115] Among them, the temperatures of the three temperature zones of the drawing tower hot stretching device 2 are: the temperature of the upper temperature zone is 210°C, the temperature of the middle temperature zone is 170°C, and the temperature of the lower temperature zone is 130°C; the drawing speed of the preform rod is 2cm / s, and the diameter of the PU melt-blown intermediate layer 7 of the prepared hollow fiber is 1.5mm;
[0116] At the same time, the liquid metal mixed solution is poured into the PU melt-blown intermediate layer 7: while the PU melt-blown intermediate layer 7 is being hot-stretched, the liquid metal mixed solution is poured into the PU melt-blown intermediate layer 7 of the PU melt-blown preform from the top opening of the PU melt-blown preform by using an injection pump, so that the pouring of the mixed solution conductive core layer 6 and the tightening and thinning of the PU melt-blown intermediate layer 7 are carried out at the same time, further enhancing the effective contact and stability between the mixed solution conductive core layer 6 and the PU melt-blown intermediate layer 7;
[0117] Among them, the injection pump flow rate of the liquid metal is 226.2 ml / h, the injection pump needle diameter is 1.5 mm, and the average diameter of the PU hollow fiber after stretching and thinning is: the inner diameter is 2 mm and the outer diameter is 2.7 mm.
[0118] S24, thermally bonding the PU melt-blown intermediate layer 7 and the aramid core-spun yarn to obtain aramid composite conductive fibers.
[0119] Aramid filaments and aramid rovings are twisted with the PU melt-blown intermediate layer 7 in the form of sirofil spinning, and the residual heat during the hot stretching process is used to make the surface of the PU melt-blown intermediate layer 7 thermally bonded with the aramid core-spun yarn in a softened state to obtain aramid composite conductive fibers;
[0120] The diameter of the aramid filament is 0.02 mm, the twisting speed of the aramid core-spun yarn is 80 TPM, and the surface temperature of the PU melt-blown intermediate layer 7 is 100° C. during thermal bonding.
[0121] Embodiment 5:
[0122] like Figure 4 and Figure 5 As shown, a preparation system of a high-performance aramid composite conductive fiber comprises:
[0123] The melt-blown cloth winding device 4 is used to wind the PU melt-blown cloth on the stainless steel pipe and is connected to the annular ultrasonic heating device 1;
[0124] The annular ultrasonic heating device 1 is used to uniformly point-bond the multi-layer PU melt-blown cloth wound on the stainless steel tube to obtain a PU melt-blown preform with uniform interlayer gaps, and is connected to the melt-blown cloth winding device 4 and the drawing tower hot stretching device 2;
[0125] The drawing tower hot stretching device 2 is used to hot stretch the prepared PU melt-blown preform rod, and is connected to the mixed solution injection device 5, the annular ultrasonic heating device 1, and the sirofil spinning device 3;
[0126] A mixed solution injection device 5 is used to inject the liquid metal mixed solution into the PU melt-blown intermediate layer 7 of the PU melt-blown preform rod, and is connected to the drawing tower hot stretching device 2;
[0127] The Serofel spinning device 3 is used to prepare aramid core-spun yarn and is connected to the drawing tower hot stretching device 2.
[0128] The meltblown cloth winding device 4 winds the PU meltblown cloth manufactured by the meltblowing process on the stainless steel tube, and the number of winding layers is several layers. After the winding is completed, the annular ultrasonic heating device 1 evenly points the multi-layer PU meltblown cloth wound on the stainless steel tube to obtain a PU meltblown preform rod with uniform interlayer gaps. The drawing tower hot stretching device 2 hangs the PU meltblown preform rod in the drawing tower hot stretching device 2, and bonds the bottom ends together. Using the principle of hot stretching, the PU meltblown preform rod is tightened and thinned until it is stretched into a fiber-like PU meltblown intermediate layer 7 While the PU melt-blown intermediate layer 7 is being hot-stretched, the liquid metal mixed solution is poured into the PU melt-blown intermediate layer 7 of the PU melt-blown preform rod from the top opening of the PU melt-blown preform rod by means of the mixed solution injection device 5, and then the aramid core-spun yarn of the sirofil spinning device 3 is put into the aramid filaments and the aramid roving are twisted with the PU melt-blown intermediate layer 7 in the form of sirofil spinning, and the residual heat during the hot stretching process is used to make the surface of the PU melt-blown intermediate layer 7 in a softened state thermally bonded with the aramid core-spun yarn to obtain the aramid composite conductive fiber.
[0129] like Figure 6 As shown, the heating part of the annular ultrasonic heating device 1 is in an annular structure.
[0130] like Figure 7 As shown, the wire drawing tower hot stretching device 2 includes: a spatial position control module 201, a laser diameter measurement and plane position measuring instrument 202, a pressure adjustment module 203, a fiber position limiting module 204, a wire drawing module 205, an inert gas delivery module 206, a heating furnace temperature control module 207, a hot stretched wire 208, a high temperature heating module 209, a preform rod suspension module 210 and a concentricity control module 211.
[0131] Among them, the spatial position control module 201 is used to control the position of the suspended PU melt-blown preform rod; the laser diameter measurement and plane position measuring instrument 202 is used to limit the diameter of the PU melt-blown preform rod during hot stretching; the pressure adjustment module 203 is used to limit the pressure of the PU melt-blown preform rod during hot stretching; the fiber position limiting module 204 is used to limit the position of the PU melt-blown preform rod during hot stretching, and the fiber position limiting module 204 can be a limiting ring; the drawing module 205 is used to wind and collect the PU melt-blown preform rod to tighten The fiber obtained after thinning, the drawing module 205 can be a drawing disk; the inert gas delivery module 206 is used to participate in controlling the hot stretching conditions of the three temperature zones; the heating furnace temperature control module 207 is used to participate in controlling the hot stretching conditions of the three temperature zones; the hot drawn wire 208 is the fiber obtained after the PU melt-blown preform rod is compacted and thinned; the high-temperature heating module 209 is used to heat the PU melt-blown preform rod; the preform rod hanging module 210 is used to hang the PU melt-blown preform rod; the concentricity control module 211 is used to fine-tune the center of the obtained fiber.
[0132] The preform hanging module 210 hangs the PU melt-blown preform. The preform hanging module 210 is provided with a high-temperature heating module 209 outside. The high-temperature heating module 209 is used to heat the PU melt-blown preform. The inert gas delivery module 206 and the heating furnace temperature control module 207 jointly control the hot stretching conditions of the three temperature zones. The fiber obtained after the PU melt-blown preform is compressed and thinned is the hot-drawn wire 208. The wire drawing module 205 winds and collects the fiber obtained after the PU melt-blown preform is compressed and thinned. The position of the suspended PU melt-blown preform is controlled by the spatial position control module 201. The laser diameter measurement and plane position measuring instrument 202 limits the diameter of the PU melt-blown preform during hot stretching. The pressure adjustment module 203 limits the pressure of the PU melt-blown preform during hot stretching. The fiber position limiting module 204 limits the position of the PU melt-blown preform during hot stretching. The concentricity control module 211 fine-tunes the center of the obtained fiber. The fiber position limiting module 204 may be a limiting ring, the wire drawing module 205 may be a wire drawing disk, and the high temperature heating module 209 may be a ZYL type high temperature heating furnace. The liquid metal mixed solution is poured from the top opening of the PU melt-blown preform into the PU melt-blown intermediate layer 7 of the PU melt-blown preform through the mixed solution injection device 5, and the mixed solution injection device 5 is provided with an injection pump.
[0133] The Sirofil spinning device 3 uses an aramid filament and aramid roving to feed the spinning frame at the same time. After being drawn, the filament is directly fed into the jaws of the front roller 304 of the spinning frame, and a certain distance is maintained with the roving fed at the same time, and twisted together to form aramid core-spun yarn. Figure 8 As shown, the sirofil spinning device 3 includes: a filament winding module 301, a roving winding module 302, a tension disk 303, a front roller 304, a guide wheel 305 and a core yarn winding module 306.
[0134] Wherein, the filament winding module 301 is used to input the winding filament;
[0135] The roving winding module 302 is used for inputting and winding roving;
[0136] A tension disk 303 is used to adjust the tension of the filaments so that the filaments are evenly arranged;
[0137] The godet 305 is used for pulling the filaments and the roving and connecting the filaments and the roving;
[0138] Front roller 304, used to twist filaments and rovings to form aramid core-spun yarn;
[0139] The core-spun yarn winding module 306 is used to sort and recycle the aramid core-spun yarn.
[0140] The filament winding module 301 inputs the winding filament, which is adjusted by the tension disk 303 and evenly passes through the guide wheel 305 and the coarse yarn to merge with the front roller 304. The coarse yarn winding module 302 inputs the winding coarse yarn, which is pulled by the guide wheel 305 and merges with the filament to the front roller 304. The front roller 304 twists the filament and the coarse yarn into aramid core-spun yarn, and the aramid core-spun yarn is sorted and recovered through the core-spun yarn winding module 306 for subsequent use.
[0141] Comparative Example 1
[0142] Different from step S1 of embodiment 2, the preparation of PU melt-blown preform in this comparative example is changed to compression molding, and step S1 is as follows:
[0143] The hollow cylindrical compression molding mold is preheated, the polyurethane material is evenly placed in the mold in the form of sheets, the mold is closed, and the material is formed into a stable cylindrical shape in the mold through high temperature and high pressure. After the polyurethane is completely cured, the pressure is gradually reduced and the mold is cooled to facilitate demoulding and maintain the product size accuracy. After demoulding, a hollow PU melt-blown preform is obtained;
[0144] The preheating temperature of the compression molding mold is 180°C, the working temperature after the mold is closed is 200°C, and the working pressure is 30MPa. The prepared PU melt-blown preform rod is a hollow column with an inner diameter of 12mm, an outer diameter of 17mm, and a height of 1.5m.
[0145] Comparative Example 2
[0146] Different from step S3 of embodiment 2, in this comparative example, the infusion of the mixed solution conductive core layer 6 and the compaction and refinement of the PU melt-blown intermediate layer 7 are no longer performed simultaneously, and step S3 is as follows:
[0147] After the PU melt-blown preform rod is completely stretched and thinned to obtain PU fibers with an average inner diameter of 2 mm and an average outer diameter of 2.7 mm, the PU fibers are suspended and the prepared liquid metal mixed solution is injected from the top until it fills the entire PU melt-blown middle layer 7 of the PU fibers.
[0148] Comparative Example 3
[0149] Different from step S4 of Example 2, the sirofil spinning is not carried out under the condition of residual heat in this comparative example, and step S4 is as follows:
[0150] When the outer surface temperature of the PU fiber is close to room temperature, the aramid filaments and aramid rovings are twisted with the PU melt-blown intermediate layer 7 in the form of sirofil spinning, so that the PU melt-blown intermediate layer 7 is twisted with the aramid core-spun yarn to form the aramid core-spun yarn skin layer 8. The diameter of the aramid filaments is 0.02 mm, the twisting speed of the aramid core-spun yarn is 80 TPM, and the temperature of the outer surface of the PU melt-blown intermediate layer 7 is 25° C. during twisting.
[0151] The high-performance aramid composite conductive fibers prepared in Examples 2 to 4 and Comparative Examples 1 to 3 were subjected to performance tests, and the test parameters included conductivity, fire rating, tensile strength at break, elongation at break, bending resistance, chemical resistance, and thermal stability;
[0152] Among them, the implementation standard of the conductivity test is GB / T 3048.4-2007; the implementation standard of the fire rating test is GB / T 5455-2014; the implementation standard of the tensile strength and elongation at break test is GB / T3923.1-2013; the implementation standard of the bending resistance test is GB / T 21196.1-2007; the test method of chemical resistance is: using an immersion test, the sample is completely immersed in a specific chemical substance for a certain period of time, and then its mass change, mechanical property loss or appearance change, etc. are evaluated; the test of thermal stability: using thermogravimetric analysis (TGA) to measure the mass change of the material during heating, which is used to evaluate the thermal decomposition temperature and thermal stability of the material. The performance test results are shown in Table 1.
[0153] Table 1 Performance test parameter value table.
[0154]
[0155] Comprehensively from the data in Table 1, it can be concluded that compared with other embodiments and comparative examples, the high-performance aramid composite conductive fiber prepared in Example 2 has more superior conductive performance, up to 1×107 Siemens per meter, which is the result of the synergistic effect of the liquid metal advantage and the magnesium nanoparticles, and the composite fiber has excellent mechanical properties, a tensile breaking strength of 3268 MPa, and compared with traditional conductive fibers and ordinary aramid composite fibers, the ductility of the aramid composite conductive fiber is also improved to 4.1%, which can effectively avoid the bending fracture and limited use problems caused by poor ductility of the conductive fiber. The number of bends in the bending resistance test is as high as 5214 times, which also proves that the thickness of the PU melt-blown intermediate layer 7 and the diameter of the composite fiber are not the decisive factors for the bending performance. The chemical resistance of Example 2 is an example of the best process parameters. In the thermal stability test, the heat resistance temperature of Example 2 is 265°C, which also shows that the thermal stability of the aramid composite conductive fiber is mainly reflected in the stability of the aramid skin-core structure shell and the composite architecture.
[0156] Compared with Example 2, the thermal stability and fire resistance level of the aramid composite conductive fiber prepared in Example 1 are reduced. Under the process conditions, the structural stability of the composite conductive fiber is significantly reduced, indicating that the production of the preform rod proposed in the present invention and the combination with the stretching and thinning method, compared with the ordinary compression molding followed by hot stretching, the layered point bonding has better structural stability and can achieve uniform and effective bonding with the aramid core-spun yarn skin layer 8. The one-piece compression molding has reduced tensile breaking strength, chemical resistance and thermal stability of the fiber produced compared to the stretching and thinning process with a uniform layered structure, further reflecting the structural advantages of the layered uniform point bonding preform rod in the stretching and thinning process.
[0157] Compared with Example 2, the conductivity of the aramid composite conductive fiber prepared in Comparative Example 2 is significantly reduced, only 5E+05S / m, which shows that the simultaneous infusion of the mixed solution conductive core layer 6 and the compaction and refinement of the PU melt-blown intermediate layer 7 is very necessary to maintain the high conductivity of the composite fiber. Filling the mixed solution conductive core layer 6 while the fiber is stretched and refined can improve the bonding and contact quality between the mixed solution conductive core layer 6 and the PU melt-blown intermediate layer 7, thereby enhancing the mechanical strength and conductivity of the overall structure. At the same time, the ineffective contact between the mixed solution conductive core layer 6 and the PU melt-blown intermediate layer 7 also leads to a significant decrease in the elongation at break, which makes the prepared composite fiber lack toughness, limiting the use scenario and service life of the composite conductive fiber.
[0158] Compared with Example 2, the mechanical properties of the aramid composite conductive fiber prepared in Comparative Example 3 are greatly reduced. The direct twisting of the aramid core-spun yarn skin layer 8 leads to a significant reduction in the composite strength and elongation at break of the aramid core-spun yarn and the PU melt-blown intermediate layer 7. The decrease in the toughness of the composite fiber also directly leads to a decrease in its bending resistance. At the same time, its chemical resistance and thermal stability are also weakened, which shows that the combination of thermal bonding and twisting does make the aramid core-spun yarn skin layer 8 and the PU melt-blown intermediate layer 7 evenly and stably combined together. This is mainly reflected in two aspects. On the one hand, the composite method can make the aramid core-spun yarn skin layer 8 and the PU melt-blown middle layer 7 more tightly and stably combined, so as to enhance the mechanical strength of the composite fiber and prevent chemical corrosives from invading the interior of the composite fiber. On the other hand, the combination of the cellulose spinning form and thermal bonding enables the PU melt-blown middle layer 7 and the aramid core-spun yarn skin layer 8 to retain a certain elongation strain capacity. The aramid core-spun yarn will be partially embedded in the PU melt-blown middle layer 7 due to thermal bonding, which also provides possible space for the elongation of the aramid core-spun yarn skin layer 8 during stretching, further improving the toughness of the composite fiber.
[0159] It should be noted that, in the present invention, the polyurethane chips are specifically 1580 type PU, the processing level is extrusion level; the hydrochloric acid solution has an equivalent concentration of 0.01 mol / L; the anhydrous ethanol has an ethanol content of 99.99%; and the magnesium nanoparticles have a particle size of nanometer level.
[0160] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0161] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing high-performance aramid composite conductive fiber, characterized in that: The following steps are involved: S1, preparing PU melt-blown preform; S2, preparing a liquid metal mixed solution; S3, while preparing the PU melt-blown middle layer, pouring the liquid metal mixed solution into the PU melt-blown middle layer; S4, thermally bonding the PU melt-blown middle layer and the aramid core-spun yarn to obtain aramid composite conductive fibers.
2. The method for preparing a high-performance aramid composite conductive fiber according to claim 1, characterized in that: The specific steps of S1 are as follows: The polyurethane slices are made into PU melt-blown cloth by melt-blowing process, and the PU melt-blown cloth is wound on the stainless steel pipe in a layered structure. The PU melt-blown cloth on the stainless steel pipe is heated by an annular ultrasonic heating device to soften and bond it, and the steel pipe is removed to obtain a PU melt-blown preform rod; Among them, the melt index of the polyurethane chip is 280g / (10min), the melt temperature is 210℃, the spinning speed is 200m / min, the wind speed is 200m / min, and the receiving distance is 20cm; the surface density of the PU meltblown cloth is 1.2-1.3g / cm3, and the thickness is 0.2-0.3mm; the outer diameter of the stainless steel tube is 12mm, the number of winding layers of the PU meltblown cloth is 5-6 layers, and the heating temperature of the annular ultrasonic heating device is 180-200℃.
3. The method for preparing a high-performance aramid composite conductive fiber according to claim 1, characterized in that: The specific steps of S2 are as follows: The gallium indium tin liquid metal is immersed in a hydrochloric acid solution, and after standing, it is washed with anhydrous ethanol, and magnesium nanoparticles are added, and stirred evenly with a magnetic stirrer to obtain a liquid metal mixed solution in which magnesium nanoparticles are evenly mixed; The concentration of the hydrochloric acid solution is 5%-20%, the concentration of anhydrous ethanol is 99.9%, the mass ratio of gallium indium tin liquid metal and magnesium nanoparticles ranges from 1:1 to 10:1, the diameter of the magnesium nanoparticles is 5-10nm, and the rotation speed of the magnetic stirrer is 600-800r / min.
4. The method for preparing a high-performance aramid composite conductive fiber according to claim 1, characterized in that: The specific steps of S3 are as follows: The bottom ends of the PU melt-blown preform rods are bonded together in a ring-shaped ultrasonic heating device, and the PU melt-blown preform rods are shrunk and thinned by the thermal stretching principle until they are stretched into a fiber-like PU melt-blown middle layer; Among them, the drawing speed is 2cm / s, the diameter of the PU melt-blown middle layer is 1.5-2.0mm, the temperature of the upper temperature zone is 190-210℃, the temperature of the middle temperature zone is 150-170℃, and the temperature of the lower temperature zone is 110-130℃; While the PU melt-blown intermediate layer is being hot-stretched, the prepared liquid metal mixed solution is infused into the PU melt-blown intermediate layer of the PU melt-blown preform from the top opening of the PU melt-blown preform by using a syringe pump; wherein the hot-stretching temperature range is 100-190°C, the diameter of the PU melt-blown intermediate layer is 0.3-0.4mm, the syringe pump flow rate is 226.2ml / h, and the syringe pump needle diameter is 1.5mm.
5. The method for preparing a high-performance aramid composite conductive fiber according to claim 1, characterized in that: The specific steps of S4 are as follows: Aramid filaments and aramid rovings are twisted with the PU melt-blown middle layer in the form of sirofil spinning, and the residual heat during the hot stretching process is used to make the surface of the PU melt-blown middle layer thermally bonded with the aramid core-spun yarn in a softened state to obtain aramid composite conductive fibers; The diameter of the aramid filament is 0.02-0.03 mm, the twisting speed of the aramid core-spun yarn is 80-100 TPM, and the surface temperature of the PU melt-blown middle layer is 140-150°C.
6. A high-performance aramid composite conductive fiber, suitable for the method for preparing a high-performance aramid composite conductive fiber as claimed in any one of claims 1 to 5, characterized in that: include: A mixed solution conductive core layer is connected to a PU melt-blown middle layer, and the PU melt-blown middle layer is thermally twisted with aramid filaments and aramid rovings by a sirofil spinning process to form an aramid core-spun yarn skin layer.
7. A high-performance aramid composite conductive fiber preparation system, applicable to a high-performance aramid composite conductive fiber preparation method as claimed in any one of claims 1 to 5, characterized in that: include: Meltblown cloth winding device, used to wind PU meltblown cloth on stainless steel pipe; The annular ultrasonic heating device is used to uniformly point-bond the PU melt-blown cloth wound on the stainless steel tube to obtain a PU melt-blown preform rod, which is connected to the melt-blown cloth winding device; The drawing tower hot stretching device is used to hot stretch the prepared PU melt-blown preform rod and is connected to the annular ultrasonic heating device; A mixed solution injection device is used to inject the liquid metal mixed solution into the PU melt-blown middle layer of the PU melt-blown preform rod, and is connected to the drawing tower hot stretching device; The Serofel spinning device is used to prepare aramid core-spun yarn and is connected to the drawing tower hot stretching device.
8. A high-performance aramid composite conductive fiber preparation system according to claim 7, characterized in that: The hot drawing device of the drawing tower includes: A spatial position control module, used to control the position of the suspended PU melt-blown preform; Laser diameter measuring and plane position measuring instrument, used to define the diameter of PU melt-blown preform during hot stretching; The pressure adjustment module is used to limit the pressure applied to the PU melt-blown preform during hot stretching; Fiber position limiting module, used to limit the position of PU melt-blown preform during hot stretching; Wire drawing module, used for winding and collecting fibers obtained after shrinking and thinning PU melt-blown preform rods; An inert gas delivery module is used to control the thermal stretching conditions in the three temperature zones; The heating furnace temperature control module is used to control the thermal stretching conditions in the three temperature zones; High temperature heating module, used to heat PU melt-blown preform; Preform hanging module, used to hang PU melt-blown preform; Concentricity control module for fine tuning the center of the produced fiber.
9. A high-performance aramid composite conductive fiber preparation system according to claim 7, characterized in that: The Serofel spinning device includes: A filament winding module, used for feeding and winding filaments; A roving winding module, used for inputting and winding roving; Tension disk, used to adjust the tension of the filaments so that the filaments are evenly set; The godet is used to draw the filaments and rovings and connect the filaments and rovings; Front roller, used to twist filaments and rovings to form aramid core-spun yarn; Core yarn winding module for finishing and recycling aramid core yarn.
Citation Information
Patent Citations
A method for preparing aramid nanofiber composite conductive fibers
CN113235184B
Filter tips used for electronic cigarettes and preparation method of filter tips
CN110477450A
Conductive fiber, spinning pack and preparation method for conductive fiber
CN111850736A
Ply twisted yarn and fabric with cutting resistance
CN112458582A
Tension sensing fiber, yarn, fabric and preparation method of tension sensing fiber
CN113201802A
Cited By
Conductive film based on liquid metal fibrosis and preparation method thereof
CN121355033A